Strengthening financial literacy of smallholder farmers through agricultural fintech peer-to-peer lending: evidence and practical implications - Muhammad Soekarni; Latif Adam; Mahmud Thoha; Jiwa Sarana; Tuti Ermawati; Yeni Saptia; Septian Adityawati; Sujianto; Mukti Wibowo (Cogent Social Sciences)
This study examined the role of agricultural financial technology (fintech), specifically peer-to-peer lending (P2PL), in strengthening small farmers’ financial literacy. Through a qualitative approach, this research collected comprehensive information from key informants, especially horticulture and aquaculture farmers who had received financial support from agricultural fintech providers in several West Java regions of Indonesia, including West Bandung, Cianjur, Sukabumi, and Bogor. The crucial finding, obtained through in-depth interviews and focus group discussions (FGDs), was that P2PL generally supported farmers with relatively low financial literacy. Interestingly, fintech plays an essential role in improving financial behaviors and attitudes. However, fintech’s efforts to improve financial literacy were primarily conducted in the initial phase. Therefore, financial literacy initiatives should be carried out systematically and sustainably. Collaborating with OJK, Central Bank, and relevant government agencies is necessary.